Perempuan Minangkabau Dalam Fotografi Masa Kolonial Tahun 1900-1942 - Ilma, Ilma (Jurnal Ceteris Paribus, 2023)
The emergence of photography can represent the opening of a new world. The main research problem is what the life of Minangkabau women was like in colonial photography, as well as explaining ideas, photo descriptions, and their relation to the reality of Minangkabau women during the colonial period. This study aims to understand the life forms of Minangkabau women in colonial photography so as to explain the symbolic interactions of Minangkabau women in photography and its historical context. This study uses the historical method which consists of four stages, namely: heuristics, criticism, interpretation, and historiography. The results showed that the photography of Minangkabau women during the colonial period showed their modern life and social status in society. Minangkabau women during the colonial period placed modernity as their new way of looking at the world, thus producing images and images of women that had both aesthetic value and reality. Keywords: Minangkabau women, photography, modernity